Consequences of the Adoption of the IADPSG versus Carpenter and Coustan Criteria to Diagnose Gestational Diabetes: A Before-After Comparison - Gariani, Karim; Egloff, Michael; Prati, Sarah; Philippe, Jacques; Boulvain, Michel; Jornayvaz, François R. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aims To evaluate if the adoption of the International Association of Diabetes and Pregnancy Study Groups (IADPSG) diagnostic criteria for Gestational Diabetes Mellitus (GDM) led to changes in the management and in the occurrence of pregnancy complications.Methods This was a retrospective study of women with GDM followed at a single university center, diagnosed in 2009–2010 using the Carpenter and Coustan criteria (period 1) and in 2012–2013 using the IADPSG criteria (period 2).Results We included 286 women with GDM, 129 in period 1 and 157 in period 2. Age, body mass index and weight gain during pregnancy were similar. There were less women requiring insulin therapy in period 2 than in period 1 (43.3% versus 55.0% respectively, p=0.048), but no significant difference in the number of cesarean section, in babies born large for gestational age and in the occurrence of preeclampsia. There was less neonatal hypoglycemia (<2.5 mmol/l) in period 2 versus period 1 (7 versus 23 neonates respectively, p<0.001).Conclusions When using the new IADPSG criteria, women with a less severe GDM are diagnosed, and fewer women require insulin. There was no difference in maternal outcomes, but less neonatal hypoglycemia during when using the IADPSG criteria.
Keywords: gestational diabetes; IADPSG; Carpenter and Coustan; screening